Bovine serum albumin-based nanoparticles containing the flavonoid rutin produced by nano spray drying - Regiellen Cristina Pedrozo; Emilli Antônio; Najeh Maissar Khalil; Rubiana Mara Mainardes (Universidade de São Paulo, 2020)
Rutin is a flavonoid compound obtained from different vegetables and fruits; specifically, it is found in the seeds of buckwheat and in fruit peels, particularly citrus. It is also an important constituent of red wine. Rutin exhibits various biological properties including antiviral, vasoprotective, anti-inflammatory, and anticarcinogenic activities. However, its antioxidant activity is the most well studied. Despite the potential for in vitro applications, rutin presents low oral bioavailability that affects its biological activities. Nanoparticles composed of polymers, protein, or lipids are of great importance in the pharmaceutical and nutraceutical areas due to their physicochemical properties, which improve the pharmacokinetics of the drug which is loaded within. This study presents the production of bovine serum albumin (BSA) nanoparticles containing rutin by nano spray drying. Nanoparticles were characterized in terms of mean particle size, size distribution, morphology, zeta potential, and drug content; as well as their antioxidant activity. The optimized spray-drying conditions produced spherical particles with a mean size of 316 nm, zeta potential of −32 mV, and encapsulation efficiency around 32%. Moreover, when antioxidant activity toward the ABTS+ radical was assayed, nanoencapsulation increased the IC50 of rutin by 2-fold. The nano spray-drying process proved to be suitable for the production of rutin-loaded BSA nanoparticles with potential antioxidant activity.